Botulinum toxin type A for amyotrophic lateral sclerosis lower limb spasm: two case reports - Qiang Duan; Chao Li; Chunxia Wei; Qian Wang; Bo Wang; Liangwen Sun; Yongjing He; Junxia Qin; Xiaoqun Huang (BMC Neurology)
Abstract Background Patients with amyotrophic lateral sclerosis (ALS) often experience spasticity, which can severely affect their ability to perform basic activities like standing and walking, potentially diminishing their already compromised quality of life. Botulinum toxin type A (BTX-A) is a first-line drug for spastic management. However, there are limited reports on its effectiveness in reducing muscle tone among ALS patients, with scarcely any related research conducted in China. We conducted the clinical observation and follow-up study through the relevant ethical post (ChiCTR2200061794). Clinical registration was on July 2, 2022. All participants provided written informed consent. Case presentation We report two cases of middle-aged male patients, both diagnosed with ALS, who presented with symptoms such as limb stiffness and walking limitation due to increased muscle tone in the lower limbs. Based on the spasticity of the patient’s lower limbs, the corresponding target muscles were selected for BTX-A treatment under ultrasound guidance, and the patients were evaluated on relevant functional scales before injection (baseline, T0) and at three follow-up visits (T1: 2 weeks, T2: 4 weeks, T3: 8 weeks). Conclusion Appropriate BTX-A injected into the target muscles could effectively depress the spasticity of ALS patients without apparent side effects.